Peran Guru Pendidikan Agama Islam dalam Memperkuat Profil Pelajar Pancasila di SMA Islam Al-Azhar 15 Semarang - Majid, Abdul; Junaedi, Mahfud; Ikhrom, Ikhrom (Jurnal Studi Guru dan Pembelajaran, 2024)
This study aims to analyse the role of Islamic Religious Education (PAI) teachers in strengthening the Pancasila student profile at Al-Azhar 15 Semarang Islamic High School. Using a qualitative research design with a case study approach, this study explores the various roles of PAI teachers, including their roles as parents, coaches, scientists, storytellers, and therapists. The study involved 3 PAI teachers with more than 5 years of teaching experience, 1 principal as a key informant, and 10 students who were actively involved. The data collection methods used were in-depth interviews, participatory observation, documentation, and questionnaires. The findings show that PAI teachers play an important role in providing emotional support, moral guidance, practical skills, leadership development, critical thinking, and addressing students' emotional and psychological challenges. Despite facing challenges such as time constraints, resources, and student resistance, PAI teachers significantly impacted students' moral awareness, social skills, leadership, and spiritual development. The findings are in line with previous research that emphasises the importance of holistic and integrative character education. This study underscores the need for support and training for PAI teachers to optimise their role and shows that religious education can significantly contribute to students' character building. Overall, PAI teachers at SMA Islam Al-Azhar 15 Semarang play an important role in shaping students' Pancasila profile, highlighting the significant contribution of religious education to students' character development.